Droplet digital PCR applied to environmental DNA, a promising method to estimate fish population abundance from humic‐rich aquatic ecosystems. Issue 2 (24th June 2020) - Capo, Eric; Spong, Göran; Koizumi, Shuntaro; Puts, Isolde; Olajos, Fredrik; Königsson, Helena; Karlsson, Jan; Byström, Pär
Abstract: Measures of environmental DNA (eDNA) concentrations in water samples have the potential to be both a cost‐efficient and a nondestructive method to estimate fish population abundance. However, the inherent temporal and spatial variability in abiotic and biotic conditions in aquatic systems have been suggested to be a major obstacle to determine relationships between fish eDNA concentrations and fish population abundance. Moreover, once water samples are collected, methodological biases are common, which introduces additional sources of variation to potential relationships between eDNA concentrations and fish population abundance. Here, we evaluate the performance of applying the droplet digital PCR (ddPCR) method to estimate fish population abundance in experimental enclosures. Using large‐scale enclosure ecosystems that contain populations of nine‐spined stickleback ( Pungitius pungitius ), we compared the concentrations of fish eDNA (COI mitochondrial region, 134 bp) obtained with the ddPCR method with high precision estimates of fish population abundance (i.e., number of individuals) and biomass. To evaluate the effects of contrasted concentrations of humic substances (potential PCR inhibitors) on the performance of ddPCR assays, we manipulated natural dissolved organic carbon (DOC) concentrations (range 4–11 mg/L) in the enclosures. Additionally, water temperature (+2°C) was manipulated in half of the enclosures. Results showed positive relationships between eDNA concentration and fish abundance and biomass estimates although unexplained variation remained. Still and importantly, fish eDNA estimates from high DOC enclosures were not lowered by potential inhibitory effects with our procedure. Finally, water temperature (although only 2°C difference) was neither detected as a significant factor influencing fish eDNA estimates. Altogether, our work highlights that ddPCR‐based eDNA is a promising method for future quantification of fish population abundance in natural systems. Abstract : We evaluated the performance of applying the droplet digital PCR (ddPCR) method to estimate fish abundance in experimental enclosures. Significant positive relationships between eDNA concentration and fish abundance and biomass were found. Additionally, fish eDNA estimates from high DOC enclosures were not lowered by potential inhibitory effects.